New auxiliary indicators for the differential diagnosis of functional cardiorespiratory limitation in patients with chronic obstructive pulmonary disease and congestive heart failure - Cesar,Marcelo de Castro (2003)
OBJECTIVE: To differentiate the nature of functional cardiorespiratory limitations during exercise in individuals with chronic obstructive pulmonary disease (COPD) or congestive heart failure (CHF) and to determine indicators that may help their classifications. METHODS: The study comprised 40 patients: 23 with COPD and 17 with CHF. All individuals underwent maximal cardiopulmonary exercise testing on a treadmill. RESULTS: The values of peak gas exchange ratio (R peak), peak carbon dioxide production (VCO2 peak), and peak oxygen ventilatory equivalent (V E O2 peak) were higher in the patients with CHF than in those with COPD, and, therefore, those were the variables that characterized the differences between the groups. For group classification, the differentiating functions with the R peak, VCO2 peak (L/min), and V E O2 peak variables were used as follows: group COPD: - 44.886 + 78.832 x R peak + 5.442 x VCO2 peak + 0.336 x V E O2 peak; group CHF: - 69.251 + 89.740 x R peak + 8.461 x VCO2 peak + 0.574 x V E O2 peak. The differentiating function, whose result is greater, correctly classifies the patient's group as 90%. CONCLUSION: The R peak, VCO2 peak, and V E O2 peak values may be used to identify the cause of the functional cardiorespiratory limitations in patients with COPD and CHF.